1997
DOI: 10.1038/ki.1997.317
|View full text |Cite
|
Sign up to set email alerts
|

Renal and systemic nitric oxide synthesis in rats with renal mass reduction

Abstract: In rats undergoing renal mass reduction (RMR) oral supplementation with the nitric oxide (NO) precursor L-arginine increases glomerular filtration rate and ameliorates signs of glomerular injury, suggesting that chronic renal failure in the rats is a condition of low NO formation in the kidney. On the contrary, data are available that in the systemic circulation of uremics, both rats and human beings, NO is formed in excessive amounts and may contribute to platelet dysfunction and bleeding tendency, well-known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
118
2
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(139 citation statements)
references
References 51 publications
16
118
2
3
Order By: Relevance
“…Paradoxic, previous studies showed elevated plasma NOx levels in patients with CKD, which was probably due to decreased excretion of NOx (46,47). To the extent that pulsatile stretch and distension of the arterial wall favor NO release in hypertension (48), it is speculated that lack of hypertension in our canine model and the subsequent reduction in systemic NO production may result in no increases in plasma NOx levels. Of note, in mild (i.e., 1/2Nx) CKD, the eNOS expression was relatively preserved, whereas the DDAH-II expression was markedly downregulated (Figure 3).…”
Section: Discussionmentioning
confidence: 72%
“…Paradoxic, previous studies showed elevated plasma NOx levels in patients with CKD, which was probably due to decreased excretion of NOx (46,47). To the extent that pulsatile stretch and distension of the arterial wall favor NO release in hypertension (48), it is speculated that lack of hypertension in our canine model and the subsequent reduction in systemic NO production may result in no increases in plasma NOx levels. Of note, in mild (i.e., 1/2Nx) CKD, the eNOS expression was relatively preserved, whereas the DDAH-II expression was markedly downregulated (Figure 3).…”
Section: Discussionmentioning
confidence: 72%
“…21 In addition, antagonism of endothelin receptors delayed the progression of renal failure, as evidenced by measurement of urinary protein and histological analysis, and increased the survival rate of rats with renal mass reduction, 39 a model characterized by an impairment of renal NO production. 40 In conclusion, our study establishes that, in preglomerular vessels, endogenous NO not only acts as a vasodilatory autacoid but also prevents the pathogenic activity of ET-1. This effect of NO is at least partially due to the inhibition of vascular ET-1 synthesis.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, deficient NO production has been described in Nx rats and could contribute to renal injury in this model (11)(12)(13). Although these data are interpreted by several investigators as indicative that progressive renal disease is a state of NO deficiency (11)(12)(13), the role of NO derived from the inducible isoform, iNOS, remains uncertain.…”
mentioning
confidence: 68%
“…In addition, deficient NO production has been described in Nx rats and could contribute to renal injury in this model (11)(12)(13). Although these data are interpreted by several investigators as indicative that progressive renal disease is a state of NO deficiency (11)(12)(13), the role of NO derived from the inducible isoform, iNOS, remains uncertain. Several studies indicated that iNOS is expressed in large amounts in the normal renal tissue, localizing mainly in the tubules, and that pathologic conditions, such as clinical and experimental chronic renal insufficiency, are associated with marked iNOS downregulation (13)(14)(15).…”
mentioning
confidence: 68%